Antología Abierta De Literatura Hispana - Ward, Julie Ann (Open textbook library., 2017)
Una antología crítica de textos literarios del mundo hispanohablante. Se enfoca en autores canónicos y también se intenta incluir voces marginadas. Cada texto tiene una introducción y anotaciones creadas por estudiantes. A critical anthology of literary texts from the Spanish-speaking world. A focus on canonical authors and an attempt to include voices that have been marginalized. Each text includes an introduction and annotations created by students.